Legal Review of Tik Tok Shop Re-Operation on The Tik Tok Social Media Application - Ramadani, Andi Andini Dwi; Jafar, Faisal Herisetiawan; Mayasari, Riezka Eka (Sangia Nibandera Law Research, 2024)
The Tiktok application, which initially only focused on entertainment through interesting videos, is starting to introduce a new feature called Tik Tok Shop, which allows users to carry out online buying and selling transactions or E-Commerce. Problems arose when the government issued Minister of Trade Regulation Number 31 of 2023 where there is a prohibition on social media platforms from doing so payment transactions on one social media application that had an impact the closure of the TikTok Shop application feature, even though we have the TikTok Shop feature returned but various issues continue to emerge such as practice monopoly, Predatory Pricing. The research method used is legal research Normative is legal research that places law as a building norm system. The norm system in question is about principles, norms, rules of legislation, court decisions, agreements, and doctrine (teaching). Based on the results of the research conducted, it was found that the application TikTok continues to carry out two types of activities, namely social media and transactions payments as well as monopolistic practices and alsoPredatory Pricing still found.